Colombian pedagogical thought: Martín Restrepo Mejía. A glance at his concepts of pedagogy, childhood, teacher and school (2017)
This article is part of a nascent line of research: History of Colombian pedagogical thought. This proposal aims to recover the work of a group of intellectuals of education; whose reflections, interventions, conferences, essays, and books have contributed to the reflective exercise upon local and regional education. This first research presents the life and work of Martín Restrepo Mejía (1865-1935), one of the first education intellectuals of Colombia. Especial emphasis is laid on his considerations and representations of pedagogy, childhood, teacher, and school education.